PANDEMI COVID-19 TERHADAP SEKTOR PARIWISATA NEGERI DI ATAS AWAN DI DESA BENTENG MAMULLU KECAMATAN KAPALA PITU KABUPATEN TORAJA UTARA - Dappa, Saena; Lasut, Jouke J.; Kandowangko, Nicolaas (HOLISTIK, Journal Of Social and Culture, 2021)
Covid-19 has become a global problem and has a huge impact on all sectors of life around the world. Starting from the economic sector, health, education, social, tourism and so on. The steps taken by the government in reducing the number of spread of the Covid-19 virus are social distancing. Social distancing is an attempt by a person not to interact at close range or avoid crowds, wash their hands, and wear masks. This policy is considere effective in reducing the spread of COVID-19.North Toraja Regency is an area famous for the term "Tondok Lilina Lepongan Bulan Tana Matari Allo", which stores a variety of riches, both natural wealth and cultural and customs that always fill every space in traditional activities contained in the lives of local people. North Toraja Regency is also one of the most famous tourist destinations in Indonesia.During the Covid-19 pandemic Lolai tourist destinations or the Land above the Clouds and several other tourist attractions in North Toraja were temporarily closed to assist the government in preventing the spread of covid-19 for almost two months, thus impacting the weakening of tourism services and economic actors, weakening tourist visits, weakening the handling and processing of tourism destination objects, and weakening the support capacity of tourism facilities and accommodation.Â Keywords: pandemic, corona, tourism